A substrate-multiplexed platform for profiling enzymatic potential of plant family 1 glycosyltransferases - Sasilada Sirirungruang; Vincent Blay; Elys P. Rodriguez; Yasmine F. Scott; Khanh M. Vuu; Collin R. Barnum; Paul H. Opgenorth; Fanzhou Kong; Yuanyue Li; Oliver Fiehn; Patrick M. Shih (Nature Communications)
Abstract Plants have expanded various biosynthetic enzyme families to produce a wide diversity of natural products; however, most enzymes encoded in plant genomes remain uncharacterized, highlighting the need for new functional genomic approaches. Here, we report a platform enabling the rapid functional characterization of plant family 1 glycosyltransferases, which serve important roles in plant development, defense, and communication. Using substrate-multiplexed reactions, mass spectrometry, and automated analysis, we screen 85 enzymes against a diverse library of 453 natural products, for a total of nearly 40,000 possible reactions. The resulting dataset reveals a widespread promiscuity and a strong preference for planar, hydroxylated aromatic substrates among family 1 glycosyltransferases. We also characterize glycosyltransferases with an unusually wide substrate scope and with a non-canonical Cys-Asp catalytic dyad. This work establishes a widely-applicable enzymatic screening pipeline, reflects the immense glycosylation capability of plants, and has implications in biocatalysis, metabolic engineering, and gene discovery.